Sacrum i antysacrum w Inwazji barbarzyńców (2003) Denysa Arcanda. W 50‑lecie europejskiej i amerykańskiej rewolucji kulturalnej [Sacrum and anti‑sacrum in The Barbarian Invasions (2003) of Denys Arcand. On the occasion of the semicentenary of the European and American cultural revolution] - Kulczycka, Dorota (Biuletyn Edukacji Medialnej [Media Education Bulletin], 2017)
In 2018, it will have been fifty years since the events that gave rise to the changes in the field of mentality, tradition, and politics. They have revolutionized the worldview of many people for the long time. In 2003, came into being two different movies on subject of the 1968 upheaval known as the cultural revolution: (France-United Kingdom-Italy 2003, directed by Bernardo Bertolucci) and The Barbarian Invasions (fr. Les invasions Barbares, France-Canada 2003, directed by Denys Arcand). The author of the article researches the latter film. She pays particular attention to the attitudes of the old hippies and flower children towards sacred values. She considers the religious, ecclesiastical and spiritual issues undertaken by the film director.
https://katalog.adlr.link/Record/ai-53-612740